Graphene Metamaterials for Intense, Tunable, and Compact Extreme Ultraviolet and X‐Ray Sources. Issue 1 (2nd October 2019) - Pizzi, Andrea; Rosolen, Gilles; Wong, Liang Jie; Ischebeck, Rasmus; Soljačić, Marin; Feurer, Thomas; Kaminer, Ido
Abstract: The interaction of electrons with strong electromagnetic fields is fundamental to the ability to design high‐quality radiation sources. At the core of all such sources is a tradeoff between compactness and higher output radiation intensities. Conventional photonic devices are limited in size by their operating wavelength, which helps compactness at the cost of a small interaction area. Here, plasmonic modes supported by multilayer graphene metamaterials are shown to provide a larger interaction area with the electron beam, while also tapping into the extreme confinement of graphene plasmons to generate high‐frequency photons with relatively low‐energy electrons available from tabletop sources. For 5 MeV electrons, a metamaterial of 50 layers and length 50 µm, and a beam current of 1.7 µA, it is, for instance, possible to generate X‐rays of intensity 1.5 × 10 7 photons sr −1 s −1 1%BW, 580 times more than for a single‐layer design. The frequency of the driving laser dynamically tunes the photon emission spectrum. This work demonstrates a unique free‐electron light source, wherein the electron mean free path in a given material is longer than the device length, relaxing the requirements of complex electron beam systems and potentially paving the way to high‐yield, compact, and tunable X‐ray sources. Abstract : The short operating wavelength of nanophotonic devices is crucial for compactness but also typically limits the interaction area and hence yield. Graphene metamaterials can enormously scale up the interaction area of plasmon‐based free‐electron light sources, paving the way to high‐yield, compact, and tunable sources of extreme ultraviolet to gamma rays.